The use of interactive maths apps to support early mathematical development in UK and Brazilian primary school children - Outhwaite, Laura A. (2019)
Developing strong mathematical skills at the start of primary school is vital for children’s later learning and development. Educational maths apps delivered on touch-screen tablet devices are suited to primary education and an emerging evidence base demonstrates their potential to support young children’s early mathematical development. The educational maths apps at the focus of thesis draw on the principles of active, engaged, meaningful, and socially interactive learning combined with curriculum-based content and specific learning goals. Using a mixed-methods, pragmatic approach and a multi-level, ecological, determinant framework, this thesis aimed to address how does app-based mathematics instruction work, who does it work for, and under what circumstances does it work?